Organizational identity, professional identity salience and internal auditors' assessments of the severity of internal control concerns. Issue 4 (8th July 2021) - Burt, Ian; Libby, Theresa
Abstract : Purpose: This paper aims to examine whether increasing the salience of the internal auditor's professional identity, defined by the expectations of their professional group, increases internal auditors' judgments of the severity of internal control concerns when their organizational identity is high. Design/methodology/approach: This paper tests the hypothesis using a laboratory experiment with internal auditors as participants. Findings: The results support the hypothesis that professional identity salience moderates the relation between organizational identity and the assessed severity of identified internal control weaknesses. Increasing the salience of professional identity results in a more severe assessment of identified internal control weaknesses when organizational identity is high than when it is low. Originality/value: Prior research in the lab and in the field provides mixed results about the impact of organizational identity on internal auditors' judgments of the severity of identified internal control concerns. This paper contributes to the discussion on this issue. In addition, the results have implications for the debate about the benefits and costs of in-house versus out-sourced internal audit functions.